Sleep Disturbances among Older Adults Following Traumatic Brain Injury - Albrecht, Jennifer S. (Int Rev Psychiatry, 2019)
Sleep disturbances are common sequelae of traumatic brain injury (TBI) that are associated with poorer recovery. This is important among older adults who fare worse following TBI relative to younger adults and have higher prevalence of sleep disorders. The objective of this study was to assess the risk of newly diagnosed sleep disorders following TBI among adults ≥65 years. Using a large commercial insurance database, we identified older adults diagnosed with TBI 2008–2014 (n=78,044) and non-TBI controls (n=76,107). First dates of diagnosis of four sleep disorders (hypersomnia, insomnia, obstructive sleep apnea, and restless legs syndrome) and a composite of any sleep disorder were identified. To compare groups, we used a difference-in-differences (DID) approach, accounting for pre-index differences between cohorts and the time trends in sleep diagnoses. Individuals with TBI were more likely to have any newly diagnosed sleep disorder before (14.1% vs. 9.4%, p<0.001) and after (22.7% vs. 14.1%, p<0.001) the index date. In fully adjusted DID models, TBI was associated with increased risk of insomnia (rate ratio (RR) 1.17; 95% confidence interval (CI) 1.08, 1.26) and any sleep disorder (RR 1.13; 95% CI 1.08, 1.19). Following TBI among older adults, screening and education on sleep disorders should be considered.